1992
DOI: 10.1080/15324989209381306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of green manuring withsesbania aculeataon physical properties of soil and on growth of wheat in rice‐wheat and maize‐wheat cropping systems in a semiarid region of India

Abstract: Cultivation of rice generally has an adverse effect on soil physical properties, which results in low yields of subsequent wheat crops. A field experiment was conducted for a 3-year period on a loamy sand soil to study the effects of green manure (Sesbania aculeata) incorporation in wetland rice and maize on soil physical properties in a semiarid region of India. The residual effect of green manuring was studied on root growth and yield of succeeding wheat crops. Growing wetland rice caused a breakdown of soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(42 citation statements)
references
References 10 publications
1
36
0
1
Order By: Relevance
“…The nutrients contributed from legumes could be partly responsible for yield improvement and up to 25% reduction of inorganic N fertilizer. These results are in agreement with the findings of many investigators (Ehsan et al, 2014;Shah et al, 2011 andBoparai et al, 1992) who reported that grain and straw yields of wheat were significantly increased due to application of green manures with inorganic fertilizers. Furthermore, Sultani et al (2004) observed that the average residual effect of green manure crops along with inorganic fertilizer was consistent and significant whereas green manuring alone had 9% residual effect on wheat growth and yield.…”
Section: Grain and Straw Yieldsupporting
confidence: 83%
See 1 more Smart Citation
“…The nutrients contributed from legumes could be partly responsible for yield improvement and up to 25% reduction of inorganic N fertilizer. These results are in agreement with the findings of many investigators (Ehsan et al, 2014;Shah et al, 2011 andBoparai et al, 1992) who reported that grain and straw yields of wheat were significantly increased due to application of green manures with inorganic fertilizers. Furthermore, Sultani et al (2004) observed that the average residual effect of green manure crops along with inorganic fertilizer was consistent and significant whereas green manuring alone had 9% residual effect on wheat growth and yield.…”
Section: Grain and Straw Yieldsupporting
confidence: 83%
“…The release of nutrients from green manures is rather slow; so it acts like a spontaneous supply of nutrients throughout the crop growth period compared to fertilizer N application. Ehsan et al (2014) and Boparai et al (1992) studied the residual effects of green manures on wheat crop and reported that incorporation of green manure (Sesbania aculeata) produced the highest plant height, spike bearing tillers m -2 , number of grains spike -1 and 1000-grain weight and increased root density of wheat grown after rice. Besides, Sultani et al (2004) observed a significant but variable effect of incorporation of various green manure legumes on wheat growth and yield and the maximum tillering as well as total biomass were produced by Sesbania incorporation.…”
Section: Growth and Yield Contributing Charactersmentioning
confidence: 99%
“…In the present study, even though fertilizer treatments were not imposed in the last year, higher yield was achieved in the organic fertilizer plots-especially in the LM plot, which achieved the highest DM yield at 22 Mg ha −1 across all plots and years (Figure 1). High yield was presumably achieved due to increased nutrient absorption capacity of a high density of roots due to improved soil physical properties [38] and continuous nutrient absorption from earlier manure input [39]. Moreover, the LM plot had higher TN and TC content at the end of the study than the other two plots ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…A wetland soil rice practice thus destroys the soil structure and creates a poor physical condition for the following wheat crop. This soil condition can reduce wheat yield (Sur et al, 1981;Boparai et al, 1992) presumably by limiting root growth and distribution (Oussible et al, 1992). For regeneration and maintenance of soil structure within this cropping system, plant residues are very important (Verma and Bhagat, 1992), but for various reason, the amount of residue being returned to the soil is not adequate.…”
Section: Conservation Tillagementioning
confidence: 99%